Pengaruh Luxury Brand, Product Variety, dan Service Quality Terhadap Customer Satisfaction - Wijaya, Jane Mac Kenzie; Widjaja, William (Universitas Dharmawangsa, 2025)
This study aims to examine the influence of luxury brand, product variety, and service quality on customer satisfaction at Sephora Jakarta. The issue addressed is the importance of understanding the factors driving customer satisfaction amid the growing competition in the beauty industry, especially with the rising dominance of local e-commerce platforms like Sociolla. A quantitative approach was used with purposive sampling involving 390 respondents who had previously shopped at Sephora Jakarta. Data were collected through online questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results show that all three variables have a positive and significant effect on customer satisfaction. Service quality emerged as the strongest factor, while luxury brand and product variety showed weaker but still significant effects. This study provides insight into the relative contributions of these three variables in the context of an international brand competing in a local market. It is recommended that Sephora focus more on improving personalized service, responsiveness, and overall shopping experience to enhance customer satisfaction.